Slang Words in Comments From People on Elon Musk's X Account - Husnul Khotimah, Shafira; Sariyati, Ice; Muhammad Fauzi, Erfan (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
Slang is an informal type of language often used in everyday communication, especially on social media. Meanwhile, X, a popular social media platform, features many comments that frequently use slang words in its threads. Thus, this study aimed to classify the types of slang word formation and the functions of slang words found in comments on X. The theoretical framework for this study included Yule's (2010) theory on types of slang words and Zhou and Fan's (2013) theory on the functions of slang expressions. The research employed a descriptive qualitative method. The data were taken from comments by users on Elon Musk's X account, uploaded by Elon Musk from July to August 2023. The findings identified several types of word formation: 1) clipping (7 data), 2) derivation (6 data), 3) acronyms (4 data), 4) borrowing (4 data), 5) coinage (2 data), 6) compounding (1 data), and 7) multiple processes (1 data). Among the types of word formation analyzed, clipping was the most common type of slang word formation found, with 7 examples identified. The main function of slang words in these comments was to express user’s feelings, especially their disappointment with the rebranding of Twitter to X. This suggests that users use slang and word creation techniques in a variety of ways, demonstrating linguistic innovation and originality in online communication. Keywords: Comments, Elon Musk, Functions, People, Slang Words, Types, X